Analysis of global competitiveness using copula-based stochastic frontier kink model - Paravee Maneejuk (2018)
© Springer International Publishing AG 2017. The competitiveness is a considerable issue for nations who rely on the international trade and hence leads to the competitiveness evaluation. This paper suggests considering a country’s productive efficiency to reflect the competitive ability. We introduce the copula-based nonlinear stochastic frontier model as a contribution to the competitiveness evaluation due to a special concern about the difference among countries in terms of size and structure of the economies. As a specific capability of this proposed model, we are able to find the different impact of inputs on output from the group of small countries to the group of large countries. Finally, this paper provides the efficiency scores according to our analysis and the overall ranking of global competitiveness.